Capitalization of Interes - Vidal Ramírez, Fernando (1968)
The accumulation of interest on an outstanding debt plus the interest accrued on the loan, better referred to as interest capitalization or anatocism, is a controversial issue in both comparative and national law. History has dealt with this issue, prohibiting it in most cases due to the burdensome and harmful consequences for the debtor; however, the new legal systems, under the influence of the Code Napoléon, have included anatocism in their legislation, but always under certain restrictions. In the Peruvian context, anatocism was regulated, later prohibited, and reintroduced. However, the regulations could not specify whether the restrictions imposed on the capitalization of interest also applied to the rest of the contracts, since they limited their application only to a limited number of contracts. In this context, this article aims to determine whether the capitalization of interest is lawful and whether the legal restrictions imposed on it are applicable to other types of contracts in the Peruvian legal system.